(3+1)-dimensional localized self-accelerating Airy elegant Ince–Gaussian wave packets and their radiation forces in free space *Project supported by the National Natural Science Foundation of China (Grant Nos. 11374108, 11374107, and 11775083), the Funds from CAS Key Laboratory of Geospace Environment, University of Science and Technology of China, and the Innovation Project of Graduate School of South China Normal University (Grant No. 2016lkxm64). (December 2017) - Li 李, Dongdong 冬冬; Peng 彭, Xi 喜; Peng 彭, Yulian 玉莲; Zhang 张, Liping 丽萍; Chen 陈, Xingyu 星宇; Zhuang 庄, Jingli 经立; Zhao 赵, Fang 方; Yang 杨, Xiangbo 湘波; Deng 邓, Dongmei 冬梅
Abstract : We construct analytically linear self-accelerating Airy elegant Ince–Gaussian wave packet solutions from (3+1)-dimensional potential-free Schrödinger equation. These wave packets have elliptical geometry and show different characteristics when the parameters ( p, m ) and ellipticity ε are adjusted. We investigate these characteristics both analytically and numerically and give the 3-dimensional intensity and phase distribution of these wave packets. Lastly, we analyze the radiation forces on a Rayleigh dielectric particle. In addition, we also find an interesting phenomenon that if the energy distribution between every part of wave packets is uneven at the input plane, the energy will be transferred between every part in the process of transmission.